Pengaruh Peran Ayah Terhadap Adaptasi Sosial Pada Anak Usia Dini Di Yayasan Nurmala Hati Jakarta Timur - Rabiah Al adawiyah; Nita Priyanti (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
People's perceptions of parenting that prioritize mothers over fathers are starting to shift. Along with the development of parenting science makes father involvement began to be applied in family education. The role of the father is needed in the process of child development. Based on previous research, the involvement of fathers in parenting in early childhood is still limited to responsibilities and decision holders that result in the presence of fathers who are limited to physical but not emotional. This research uses a quantitative approach. This study aims to find out the influence of the role of fathers on social adaptation in early childhood at The Nurmala Hati Foundation in East Jakarta. Based on the results of the study, the significance value of p = 0.000 and the correlation value (r) of 0.498 which means that there is a significant moderate influence between the role of fathers on social adaptation in early childhood, while the value of R square (r²) was obtained by 0.248 which shows that the percentage of the influence of father's role on social adaptation in early childhood is 24.8% at nurmala hati Foundation in East Jakarta.